Do Emotion Dysregulation, Alexithymia and Personality Dimensions Explain the Association Between Attention-Deficit/Hyperactivity Disorder and Binge Eating Among Bariatric Surgery Candidates? - El Archi, Sarah; Brunault, Paul; De Luca, Arnaud; Cortese, Samuele; Hankard, Régis; Bourbao-Tournois, Céline; Ballon, Nicolas; Réveillère, Christian; Barrault, Servane (Frontiers in Psychology, 2021)
Background: Addictive-like eating and attention-deficit/hyperactivity disorder (ADHD) are both common among persons seeking treatment for severe obesity. Given that ADHD and addictive-like eating, especially binge eating (BE) and food addiction (FA), are both strongly associated with personality dimensions and emotion dysregulation, it is possible emotional and personality characteristics contribute to the link between addictive-like eating behaviors and ADHD in people with severe obesity. This study aimed to investigate the psychological factors associated with BE and FA in bariatric surgery candidates, and to explore the mediational role of emotional factors (emotion dysregulation and alexithymia) and personality dimensions in the association between ADHD and BE. Method: Two hundred and eighty-two (n = 282) bariatric surgery candidates were recruited during the systematic preoperative psychiatric assessment (University Hospital of Tours, France). We assessed significant BE (Binge Eating Scale), probable adult ADHD (Wender Utah Render Scale and Adult ADHD Self-Report Scale), FA (Yale Food Addiction Scale 2.0, YFAS 2.0), emotion dysregulation (Difficulties in Emotion Regulation Scale-16), alexithymia (Toronto Alexithymia Scale-20) and personality dimensions (Big Five Inventory). Mediation analyses were performed using the PROCESS macro for IBM SPSS Statistics 22. Results: Prevalence of probable adult ADHD, significant BE and FA were 8.2, 19.1, and 26.6%, respectively. Participants who screened positive for addictive-like eating showed higher prevalence of probable adult ADHD, as well as higher scores on adult and childhood ADHD symptoms. They also reported lower conscientiousness, but higher emotion dysregulation, higher alexithymia, and higher neuroticism. Only BE (as opposed to FA) was also associated with lower scores on agreeableness and openness. Analysis of the association between adult ADHD and BE suggests that emotion dysregulation, conscientiousness, agreeableness, and neuroticism are total mediators and alexithymia a partial mediator. Conclusion: Our findings suggest a significant association between ADHD and addictive-like eating among bariatric surgery candidates, and also suggest a significant role of emotion dysregulation and personality dimensions in this association. For individuals with ADHD and obesity, eating may be a way to cope with negative emotions, potentially increasing the risk for addictive-like eating behavior.